FREQUENCY OF DIFFERENT GRADES OF RETINOPATHY IN HYPERTENSIVE PATIENTS AT MILITARY HOSPITAL RAWALPINDI: Retinopathy in Hypertensive Patients - Khan, Maj Abid ullah; Hussain, Muhammad Zahid; Tariq, Khalid Mehmood; Qadir, Adnan; Iqbal, Muhammad (Pakistan Armed Forces Medical Journal, 2012)
Objective: To determine the frequency of different grades of retinopathy in hypertensive patients. Design: Cross sectional study. Place and Duration of Study: Military Hospital Rawalpindi, June 2010 to December 2010. Methods: One hundred and ninety four patients with hypertension were divided into four different types of retinopathy, based on history, clinical examination (ophthalmological) and laboratory investigations. Results: Maximum number of patients were in grade II hypertensive retinopathy – i.e., 25.8 % (50 cases- 33 males and 17 females). A total of 45.9% (89 cases- 60 males and 29 female) of the patients did not have any evidence of hypertensive retinopathy, other patients had grade I, 21.1% (41 cases -31 male and 10 female), grade III, 5.7% (11 cases- 9 male and 2 female) and grade IV, 1.5% (3 cases-2 male and 1 female) at the time of examination. Conclusion: Hypertensive patients have a high incidence of retinopathy which is an important indicator of target organ damage. Therefore early diagnosis and treatment of hypertension in time can decrease morbidity due to retinopathy which is an important cause of blindness in hypertensive patients.